Federalism and the welfare state : new world and European experiences - Obinger, Herbert, 1970-; Leibfried, Stephan, 1944-; Castles, Francis Geoffrey (Cambridge University Press, 2005)
This unique and provocative volume written by ten leading experts is a comparative study of the evolution of political institutions and welfare states in the six oldest federal states - Australia, Austria, Canada, Germany, Switzerland and the US. The study reveals that federalism impedes and facilitates social policy development.